EDUCATION AND HUMAN DEVELOPMENT. A HUMAN EDUCATIONAL PURPOSE IN LATINAMERICA - Camilo Noguera Pardo, Liliana Beatriz Irizar, Javier Nicolás González Camargo, (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2011)
The aim of this paper is to analyze the link between education and development starting from a critical vision of the anthropological approach which has been guiding education in Latin-America. As an alternative of the current way of approaching that relationship, we propose a humanistic vision of education which recognizes as primary premise the spiritual condition of human being, the understanding of freedom as liberation of oneself and human people’s capacity to leader their own life and help others to direct their lives according to a wise way of thinking and living thank to intellectual and moral virtues. Civic Humanism is the philosophical-political background of this humanistic education proposal.